Fine tuning of the temporal expression of HTLV-1 and HTLV-2 - Cavallari, Ilaria; Rende, Francesca; Bender, Cecilia; Romanelli, Maria G.; D'Agostino, Donna M.; Ciminale, Vincenzo (Frontiers in Microbiology, 2013)
Human T-cell leukemia virus types 1 and 2 (HTLV-1 and HTLV-2) are deltaretroviruses that share a common overall genetic organization, splicing pattern, and ability to infect and immortalize T-cells in vitro. However, HTLV-1 and HTLV-2 exhibit a clearly distinct pathogenic potential in infected patients. To find clues to the possible viral determinants of the biology of these viruses, recent studies investigated the timing of expression and the intracellular compartmentalization of viral transcripts in ex-vivo samples from infected patients. Results of these studies revealed a common overall pattern of expression of HTLV-1 and -2 with a two-phase kinetics of expression and a nuclear accumulation of minus-strand transcripts. Studies in cells transfected with HTLV-1 molecular clones demonstrated the strict Rex-dependency of this "two-phase" kinetics. These studies also highlighted interesting differences in the relative abundance of transcripts encoding the Tax and Rex regulatory proteins, and that of the accessory proteins controlling Rex expression and function, thus suggesting a potential basis for the different pathobiology of the two viruses.